Crianças usuárias de implante coclear: desempenho acadêmico, expectativas dos pais e dos professores - Brazorotto, Joseli Soares (2008)
Cochlear implant (C.I) is one of the technological resources currently used in the (re)habilitation of deaf and hard-of hearing children. Follow-up studies have carried through, in search of evaluating which results in auditory abilities and oral language are reached for cochlear implanted children. However, concerning to the academic performance of such children the developed works are scarce, especially in Brazil.The aims of this study were to describe and analyze the academic performance of cochlear implanted children, with ages varying from 6 to 12 and carry out results associations analysis of academic performance considering the follow independent variables: age, grade, detection threshold´s voice, time of cochlear implant use, time of sensorial privation, and the biggest level´s school of the family. Moreover, this study also verified the parent´s and teacher´s informations and expectatives concerning to academic performance of this children. To reaches this aim it was done collection and analyse of datas from those children, individual evaluations of academic performance by means of standardy tests and at same time, was applied handbooks with parents and teachers of children took part in. Dates were analysed quantitative and qualitative and was applied the appropriate statistic treatment. Results showed that cochlear implanted children had smaller performance from the normality to they age and grade and statistically association was identificated between the TDE tests scores and the grade. Concerning to the parents opinions it was noticed the mainly worries refered to reading and writing learning, classroom´s activities participation as listeners pupils and also concerns about broke´s gadget (C.I.).Regarding to the informations and expectations of theachers, the conclusions are that it was scarcing of information regarding the cochlear implant, and the potential for the learning of the cochlear implanted children was considered the same or lower than average, nevertheless, it was also verified positive expectations with reference to the cochlear implanted chidren learning potential, specially to the youngest children.